2005
DOI: 10.21273/horttech.15.3.0463
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of a Gardening and Nutrition Program with a Standard Nutrition Program in an Out-of-school Setting

Abstract: After-school time is currently underutilized as a potential setting to promote healthy eating in children. Two programs, a standard nutrition program titled Professor Popcorn (PP) and a gardening and nutrition program using lessons from Junior Master Gardener: Health and Nutrition from the Garden (JMG), were compared to investigate their influence on nutrition knowledge, improving fruit and vegetable preference, and improving self-efficacy in gardening and eating fruit and vegetables in an out-of-schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 26 publications
2
38
1
Order By: Relevance
“…Youth gardening programs and projects were found to produce positive dietary, academic, and developmental results. Gardening-enhanced nutrition programs increased participants' nutrition knowledge; fruit and vegetable consumption, preference, and asking behaviors at home; physical activity; and gardening self-efficacy Poston et al, 2005;. Two studies showed no differences between students participating in a garden-enhanced nutrition program versus only the nutrition education component, except that youth in the gardenenhanced programs increased their preference for a greater number of types of vegetables .…”
Section: Published Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Youth gardening programs and projects were found to produce positive dietary, academic, and developmental results. Gardening-enhanced nutrition programs increased participants' nutrition knowledge; fruit and vegetable consumption, preference, and asking behaviors at home; physical activity; and gardening self-efficacy Poston et al, 2005;. Two studies showed no differences between students participating in a garden-enhanced nutrition program versus only the nutrition education component, except that youth in the gardenenhanced programs increased their preference for a greater number of types of vegetables .…”
Section: Published Resultsmentioning
confidence: 96%
“…Studies were considered a case study if they provided an in-depth analysis of a community garden as a whole or a component of a single or small number of gardens or garden networks; 40% of the articles fit this criteria Campbell & Salus, 2003;Doyle & Krasney, 2003;Glover, 2003Glover, , 2004Glover, Parry, & Shinew, 2005;Henderson & Harsfield, 2009;Hess & Winner, 2007;Kurtz, 2001;Langhout et al, 2002;Lawson, 2007;Macias, 2008;Roubanis & Landis, 2007;SaldivarTanaka & Krasny, 2004;Schmelzkopf, 2002;Smith & Kurtz, 2003;Staeheli, Mitchell, & Gibson, 2002;Teig et al, 2009;Twiss et al, 2003). Intervention studies looked at community gardens as a tool for manipulating some variable (e.g., diet, collective efficacy, access to food) within a population, and made up 45% of the studies reviewed (Alaimo, Packnett, Miles, & Kruger, 2008;Armstrong, 2000a;Austin et al, 2006;D'Abundo & Carden, 2008;Glover, Shinew, & Parry, 2005;Heim et al, 2009;Hermann et al, 2006;Hoffman, Knight, & Wallach, 2007;Klemmer et al, 2005;Koch et al, 2006;Morris et al, 2001;Ohmer, Meadowcroft, Freed, & Lewis, 2009;Parmer et al, 2009;Poston et al, 2005;Shinew, Glover, & Parry, 2004;L. L. Smith & Motsenbocker, 2005;Waliczek & Zajicek, 1999).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Articles were searched using following keywords: urban agriculture, urban youth, fruit and vegetable consumption, food access, community gardens, food availability, food choices, food access, food behavior, healthy eating, diet, food consumption.) Some papers focus on gardening programs based in schools, 30,34,37,38 some on after-school settings, 5,10,36,37 and some on community settings. 32,33,39,40 Programs studied in these papers range from 3-day to year-long initiatives.…”
Section: Youth Food Behaviors and Urban Agriculture: A Review Of The mentioning
confidence: 99%